The root-knot nematode, Meloidogyne incognita, profoundly affects the production of popular biofortified cassava cultivars - Akinsanya, A.K.; Afolami, S.O.; Kulakow, Peter A.; Coyne, D. (Brill, 2020)
Despite being the single largest cassava-producing country, yields in Nigeria remain consistently poor and among the lowest. Regionally, yields are also particularly low across Africa. Pests and pathogens, including plant-parasitic nematodes, play an important role in this current yield deficit. African countries are not only faced with the problem of food security but also that of nutritional deficiency, due to limited micronutrients in the diet. In this study, six biofortified cultivars were evaluated for their response to inoculation with approximately 30 000 root-knot nematode (Meloidogyne incognita) eggs in 30 l pots in Nigeria. All cassava cultivars proved highly susceptible to M. incognita infection after 6 months, with nematode reproduction factor ranging from 7.0 to 44.8. Galling was common on feeder roots and gall index scores were recorded between 4 to 5 (on a scale of 1-5 where 5 ⩽ 100 galls). Meloidogyne incognita infection significantly reduced plant height, stem girth, fresh plant mass, fresh storage root number and storage root weight. Percentage yield loss of between 41.8-88.4% was recorded in M. incognita-infected plants compared with non-infected controls. Although M. incognita reduced storage root weight, it did not necessarily affect the nutritional quality (total carotenoid) or dry weight percentage of the biofortified cassava cultivars. Total carotenoid and dry weight contents of the control cultivar were similar to some of the biofortified cultivars. The high susceptibility of the biofortified cassava cultivars to M. incognita infection indicates that substantial yield losses are likely being experienced by farmers, as this nematode pest is prevalent across sub-Saharan Africa and the tropics.